(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
Raising awareness of health technology among students in underserved regions is crucial to building future-ready healthcare ecosystems. This community engagement project aimed to enhance vocational high school students’ in rural setting understanding of medical device prototyping through a hands-on workshop on IoMT-based technologies using NodeMCU. A pre- and post-workshop assessment was conducted using the Health Technology Awareness Index (HTAI) and a participant satisfaction questionnaire. Initial findings revealed that 73.3% of students fell into the low and very low awareness categories. After the intervention, participants demonstrated a statistically significant improvement in awareness scores (p < 0.01), with an average increase of 21.4%. Satisfaction data indicated that 56.7% of participants were satisfied with the workshop, especially regarding the clarity of materials and prototype practicality. These results highlight the effectiveness of practical, locally grounded health tech workshops in narrowing the digital divide, suggesting a scalable model for future initiatives.